2011
DOI: 10.1186/1472-6947-11-43
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of use and non-use of a web-based communication system in cerebral palsy care: evaluating the association between professionals' system use and their a priori expectancies and background

Abstract: BackgroundPreviously we described parents' and professionals' experiences with a web-based communication system in a 6-month pilot in three Dutch cerebral palsy care settings. We found that half of the participating professionals had not used the system, and of those who had used the system one third had used it only once. The present study aimed to evaluate whether professionals' system use was associated with their a priori expectancies and background.MethodsProfessionals who had not used the system (n = 54)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Barnett et al [28] investigated the abilities and interests of family practice trainees and trainers and found that participants in the earlier stages of their careers were more receptive to using online forums than those who were more experienced. Gulmann et al [29] compared the use and the background characteristics of users and non-users of a web-based platform designed for health providers managing children with cerebral palsy. In addition to finding that web-based platform users had fewer years working with this population, they also found that they tended to be from rural care regions, practiced in rehabilitation centres, and had a higher number of clients with the condition compared to non-users [29].…”
Section: Demographic Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Barnett et al [28] investigated the abilities and interests of family practice trainees and trainers and found that participants in the earlier stages of their careers were more receptive to using online forums than those who were more experienced. Gulmann et al [29] compared the use and the background characteristics of users and non-users of a web-based platform designed for health providers managing children with cerebral palsy. In addition to finding that web-based platform users had fewer years working with this population, they also found that they tended to be from rural care regions, practiced in rehabilitation centres, and had a higher number of clients with the condition compared to non-users [29].…”
Section: Demographic Differencesmentioning
confidence: 99%
“…Gulmann et al [29] compared the use and the background characteristics of users and non-users of a web-based platform designed for health providers managing children with cerebral palsy. In addition to finding that web-based platform users had fewer years working with this population, they also found that they tended to be from rural care regions, practiced in rehabilitation centres, and had a higher number of clients with the condition compared to non-users [29]. Although our study highlighted similar trends (i.e., predominance of rural clinicians, working in rehabilitation settings, higher developmental coordination caseload composition), differences in these variables were not statistically significant between physiotherapists' users and non-users.…”
Section: Demographic Differencesmentioning
confidence: 99%